Electrode assembly, battery and power-using device

By applying functional coatings of thiol-based sodium salts and binders on the lithium-ion battery separator, the problem of insufficient antioxidant performance of the separator is solved, significantly improving the service life and safety of the battery, and improving the efficiency of the first circle of Coulomb.

CN119275492BActive Publication Date: 2025-04-08JIANGSU ZENIO NEW ENERGY BATTERY TECH CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411783736.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-12-06
Publication Date
2025-04-08
Estimated Expiration
2044-12-06

AI Technical Summary

Technical Problem

The existing lithium-ion battery separators have low oxidation resistance, which leads to oxidation during use, reducing their ionic conductivity, and thus affecting the battery's service life and safety.

Method used

A functional coating is provided on the separator of the battery, which contains thiol-based sodium salts and binders, and the antioxidant properties of the separator are enhanced by these materials.

Benefits of technology

By enhancing the antioxidant performance of the diaphragm, inhibiting yellowing of the diaphragm, improving its ionic conductivity, extending the service life of the battery, improving the safety of the battery, reducing the charge and discharge loss of the first circle, and improving the efficiency of the first circle Coulomb.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119275492B_ABST
    Figure CN119275492B_ABST
Patent Text Reader

Abstract

The present invention discloses an electrode assembly, a battery and an electrical device, which are used to solve the technical problem that the existing battery separator has low antioxidant performance and is often oxidized during use, thereby causing the battery separator ion conductivity to decrease. The present invention includes a positive electrode sheet, a negative electrode sheet and a separator located between the positive electrode sheet and the negative electrode sheet, characterized in that a functional coating is provided on the separator, and the functional coating includes a thiol sodium salt and a binder. Through the above design, a functional coating containing a thiol sodium salt is provided on the separator. Due to the presence of thiol, the antioxidant property of the separator surface is enhanced, the yellowing of the separator is effectively suppressed, the ionic conductivity of the separator is improved, and the service life and safety of the battery are ensured.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of battery design, and in particular to an electrode assembly, a battery and an electrical device. Background Art

[0002] Since Sony invented lithium-ion batteries in 1991, they have been widely used in all aspects of life, from mobile phones and computers to electric vehicles. With the continuous development of electronic devices or electric vehicles, the requirements for battery energy density, cycle stability, capacity, safety and other performance are getting higher and higher. Lithium-ion batteries with ternary materials as positive electrode materials have attracted attention as a high energy density and high capacity battery.

[0003] However, there are still some disadvantages in the use of ternary lithium batteries, such as the Ni in the ternary positive electrode material. 3+ / 4+ and Co 3+ / 4+ There is an energy band overlap with O. When lithium is removed during battery charging, part of O will escape from the crystal lattice in the form of free radicals, which is extremely oxidizing. The diaphragm is oxidized, causing it to turn yellow and the ionic conductivity of the diaphragm to decrease, reducing the service life and safety of the battery.

[0004] Therefore, finding a technical solution that can solve the above technical problems has become an important topic studied by technical personnel in this field. Summary of the invention

[0005] The invention discloses an electrode assembly, a battery and an electrical device, which are used to solve the technical problem that the existing battery separator has low antioxidant performance and is often oxidized during use, thereby causing the battery separator ion conductivity to decrease.

[0006] The present invention provides an electrode assembly, comprising a positive electrode sheet, a negative electrode sheet and a separator located between the positive electrode sheet and the negative electrode sheet, wherein a functional coating is provided on the separator, and the functional coating comprises a thiol sodium salt and a binder.

[0007] Optionally, the positive electrode sheet, the negative electrode sheet and the separator are wound to form the electrode assembly, the electrode assembly has a straight portion and a bent portion, and the functional coating is disposed on the bent portion.

[0008] Optionally, the functional coating is provided on a surface of the separator facing the positive electrode sheet.

[0009] Optionally, the functional coating is provided on one surface of the diaphragm facing the positive electrode sheet and on one surface of the diaphragm facing the negative electrode sheet; the thickness of the functional coating on the one surface of the diaphragm facing the positive electrode sheet is A, and the thickness of the functional coating on the one surface of the diaphragm facing the negative electrode sheet is B, wherein: 6μm≥A>B≥2μm.

[0010] Optionally, the positive electrode sheet, the negative electrode sheet and the separator are wound to form the electrode assembly, and the electrode assembly has a straight portion and a bent portion, and both the bent portion and the straight portion are provided with the functional coating; the thickness of the functional coating on the bent portion is C, and the thickness of the functional coating on the straight portion is D, wherein 6μm≥C>D≥2μm.

[0011] Optionally, the functional coating is provided on one surface of the diaphragm facing the positive electrode sheet and on one surface of the diaphragm facing the negative electrode sheet; in the bent portion, the thickness of the functional coating on the one surface of the diaphragm facing the positive electrode sheet is E, and the thickness of the functional coating on the one surface of the diaphragm facing the negative electrode sheet is F; in the straight portion, the thickness of the functional coating on the one surface of the diaphragm facing the positive electrode sheet is G, and the thickness of the functional coating on the one surface of the diaphragm facing the negative electrode sheet is H, wherein 6μm≥E>F>G>H≥2μm.

[0012] Optionally, the thiol sodium salt includes sodium dimercaptopropanesulfonate, sodium dimercaptosuccinate, sodium dimercaptosuccinate, monosodium 5-mercapto-1,2,3-triazole, sodium 3-mercapto-1-propanesulfonate, sodium thioglycolate, monosodium 2-mercaptoethanol, monosodium 2,4,6-trimercapto-1,3,5-s-triazine, sodium mercaptobenzothiazole, disodium 1-sulfonic acid methyl-5-mercaptotetrazole, disodium 5-mercapto-1-sulfonic acid methyl tetrazole, disodium 2,5-dimercaptothiadiazole, sodium 1-2-hydroxyethyl-5-mercapto-1H-tetrazole, sodium 3-mercapto-1-propanesulfonate, sodium 2-thiopyridine nitrogen oxide, tetrasodium 1,2,4,5-tetramercaptobenzene, sodium 1-methyl-5-mercaptotetrazole, trisodium mercapto-s-triazine; and / or,

[0013] The binder includes one or more of polytetrafluoroethylene, polyvinylidene fluoride, styrene-butadiene rubber, sodium carboxymethyl cellulose, polyacrylate, and polyacrylic acid; and / or,

[0014] In the functional coating, the mass ratio of the mercapto sodium salt to the binder is 40-60:5-20.

[0015] The present invention provides a battery, comprising the above-mentioned electrode assembly.

[0016] Optionally, the battery further includes an electrolyte, the electrolyte includes a solvent, and the solvent includes at least one of ethylene carbonate, diethyl carbonate, dimethyl carbonate, ethyl methyl carbonate, and vinylene carbonate.

[0017] The present invention provides an electrical device, comprising the battery.

[0018] Compared with the prior art, the present invention has the following beneficial effects:

[0019] The electrode assembly of the present invention comprises a positive electrode sheet, a negative electrode sheet and a diaphragm located between the positive electrode sheet and the negative electrode sheet, and a functional coating is arranged on the diaphragm, and the functional coating comprises a thiol sodium salt and a binder. Through the above design, a functional coating containing a thiol sodium salt is arranged on the diaphragm. Due to the presence of thiol groups, the oxidation resistance of the surface of the battery diaphragm is enhanced, the yellowing of the battery diaphragm is effectively suppressed, the ionic conductivity of the battery diaphragm is improved, and the service life and safety of the battery are ensured. In addition, the thiol sodium salt in the functional coating can also complex the positive electrode metal ions, suppressing the problems of lithium precipitation and increased internal resistance caused by metal ions. At the same time, due to the hydrophilicity of the thiol sodium salt, the wettability of the electrolyte is effectively improved. In addition, the sodium ions contained in the thiol sodium salt can reduce the sodium lost in the first cycle of charge and discharge, and improve the first cycle coulomb efficiency. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0021] Figure 1 A schematic diagram of the cross-sectional structure of a diaphragm in an electrode assembly provided by the present invention;

[0022] Illustration: diaphragm 1; functional coating 2. DETAILED DESCRIPTION

[0023] The invention discloses an electrode assembly, a battery and an electrical device, which are used to solve the technical problem that the existing battery separator has low antioxidant performance and is often oxidized during use, thereby causing the battery separator ion conductivity to decrease.

[0024] In order to enable those skilled in the art to better understand the scheme of the present invention, the present invention is further described in detail below in conjunction with the accompanying drawings and specific implementation methods. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0025] See also Figure 1 An electrode assembly provided by an embodiment of the present invention includes a positive electrode sheet, a negative electrode sheet, and a separator located between the positive electrode sheet and the negative electrode sheet, wherein a functional coating is provided on the separator, and the functional coating includes a thiol sodium salt and a binder.

[0026] Through the above arrangement, a functional coating containing sodium thiol salt is provided on the diaphragm. Due to the presence of thiol, the oxidation resistance of the surface of the battery diaphragm is enhanced, the yellowing of the battery diaphragm is effectively inhibited, the ion conductivity of the battery diaphragm is improved, and the service life and safety of the battery are ensured.

[0027] In addition, the thiol sodium salt in the functional coating can also complex the positive electrode metal ions to prevent the positive electrode metal ions from entering the negative electrode area, causing the negative electrode to produce SEI film thickening and lithium ion accumulation problems, resulting in an increase in the internal resistance of the battery and lithium precipitation problems, thereby causing the battery's electrical performance to decline.

[0028] At the same time, due to the hydrophilicity of thiol sodium salts, the wettability of the electrolyte is effectively improved. In addition, the sodium ions contained in thiol sodium salts can reduce the sodium loss in the first cycle of charge and discharge, and improve the first cycle coulomb efficiency.

[0029] It should be noted that the full name of SEI (Solid Electrolyte Interphase) membrane is "solid electrolyte interface membrane". During the first charge and discharge process of liquid lithium-ion batteries, the electrode material and the electrolyte react at the solid-liquid interface to form a passivation layer covering the surface of the electrode material. This passivation layer is an interface layer that has the characteristics of a solid electrolyte. It is an electronic insulator but Li + Excellent conductor, Li + It can be freely embedded and extracted through this passivation layer, which is called SEI film.

[0030] Furthermore, in the first specific embodiment, the positive electrode sheet, the negative electrode sheet and the separator in this embodiment are wound to form the electrode assembly, and the electrode assembly has a straight portion and a bent portion. In view of the phenomenon that positive electrode metal ions and oxygen are more likely to accumulate at the bent portion, the functional coating is arranged at the bent portion.

[0031] Among them, in this specific embodiment, since the metal ions mainly come from the positive electrode, it is necessary to prevent the metal ions from entering the negative electrode, and when the positive electrode is delithiated, O will escape from the lattice in the form of free radicals, which has extremely strong oxidizing properties, so it is preferred that the functional coating is provided on the surface of the side of the diaphragm facing the positive electrode sheet.

[0032] In addition, the functional coating can be provided on both side surfaces of the diaphragm. Specifically, the functional coating is provided on the side surface of the diaphragm facing the positive electrode sheet and the side surface of the diaphragm facing the negative electrode sheet; the thickness of the functional coating on the side surface of the diaphragm facing the positive electrode sheet is A, and the thickness of the functional coating on the side surface of the diaphragm facing the negative electrode sheet is B, wherein: 6μm≥A>B≥2μm.

[0033] It should be noted that although the metal ions and oxygen mainly come from the positive electrode, some metal ions and oxygen still pass through the diaphragm and reach the negative electrode side. Therefore, in this specific implementation, 6μm≥A>B≥2μm is set. While ensuring the energy density, the metal ion and oxygen content on the positive and negative electrode sides of the diaphragm can be effectively matched, thereby reducing the lithium plating problem of the battery during use and improving the electrical performance of the battery.

[0034] Optionally, in a second specific embodiment, the positive electrode sheet, the negative electrode sheet and the separator in this embodiment are wound to form the electrode assembly, and the electrode assembly has a straight portion and a bent portion. In view of the presence of positive metal ions and oxygen in the straight portion, the bent portion and the straight portion are both provided with the functional coating; the thickness of the functional coating of the bent portion is C, and the thickness of the functional coating of the straight portion is D, wherein 6μm≥C>D≥2μm. Through the relationship between the thickness of the functional coating of the straight portion and the bent portion, the metal ion and oxygen content of the bent portion and the straight portion of the separator can be effectively matched while ensuring the energy density, thereby reducing the problem of lithium precipitation during the use of the battery and improving the electrical performance of the battery.

[0035] Specifically, the functional coating is provided on one surface of the diaphragm facing the positive electrode sheet and on one surface of the diaphragm facing the negative electrode sheet; in the bent portion, the thickness of the functional coating on the one surface of the diaphragm facing the positive electrode sheet is E, and the thickness of the functional coating on the one surface of the diaphragm facing the negative electrode sheet is F; in the straight portion, the thickness of the functional coating on the one surface of the diaphragm facing the positive electrode sheet is G, and the thickness of the functional coating on the one surface of the diaphragm facing the negative electrode sheet is H, wherein 6μm≥E>F>G>H≥2μm.

[0036] It should be noted that, in this specific implementation, setting 6μm≥E>F>G>H≥2μm can effectively match the metal ion and oxygen content on the positive and negative electrode sides and the bent and straight parts of the diaphragm while ensuring the energy density, thereby reducing the lithium plating problem of the battery during use and improving the electrical performance of the battery.

[0037] It should be further explained that, in the above two specific embodiments, the electrical performance of the battery using the separator can be guaranteed, and at the same time, the battery has a more excellent service life, safety and first-cycle coulombic efficiency.

[0038] Further, the thiol sodium salt in this embodiment includes sodium dimercaptopropanesulfonate, sodium dimercaptosuccinate, sodium dimercaptosuccinate, 5-mercapto-1,2,3-triazole monosodium, sodium 3-mercapto-1-propanesulfonate, sodium thioglycolate, 2-mercaptoethanol monosodium, 2,4,6-trimercapto-1,3,5-s-triazine monosodium, sodium mercaptobenzothiazole, 1-sulfonic acid methyl-5-mercaptotetrazole disodium, 5-mercapto-1-sulfonic acid methyl tetrazolium disodium, 2,5-dimercaptothiadiazole disodium, 1-2-hydroxyethyl-5-mercapto-1H-tetrazole sodium, 3-mercapto-1-propanesulfonate, 2-thiopyridine sodium trinitroxide, 1,2,4,5-tetramercaptobenzene tetrasodium, 1-methyl-5-mercaptotetrazole sodium, and one or more of trisodium mercapto-s-triazine.

[0039] It should be noted that this embodiment does not limit the specific type of thiol sodium salt, and designers can select a suitable type of thiol sodium salt according to actual conditions.

[0040] Furthermore, the binder in this embodiment includes one or more of polytetrafluoroethylene, polyvinylidene fluoride, styrene-butadiene rubber, sodium carboxymethyl cellulose, polyacrylate, and polyacrylic acid.

[0041] It should be noted that this embodiment does not limit the specific type of adhesive, and designers can select a suitable type of adhesive according to actual conditions.

[0042] Preferably, the binder is one or more of sodium carboxymethyl cellulose and polyacrylic acid. Sodium carboxymethyl cellulose and polyacrylic acid contain not only hydroxyl functional groups (-OH) but also carboxyl functional groups. Using them as binders in slurry preparation is beneficial to improving the fluidity of the slurry.

[0043] Furthermore, in the functional coating of this embodiment, the mass ratio of the thiol sodium salt to the binder is 40-60:5-20.

[0044] Illustratively, the mass ratio of the thiol sodium salt to the binder can be 40:5, 40:10, 40:15, 40:20, 50:5, 50:10, 50:15, 50:20, 60:5, 60:10, 60:15, 60:20 or any value within the range consisting of any two of the above values.

[0045] The mass ratio of the thiol sodium salt to the binder is set within this range. If the mass ratio is too small, the thiol sodium salt will have little effect on the separator, that is, the battery, and will not play a substantial role; if the mass ratio is too large, the bonding performance of the functional coating will be reduced, resulting in a decrease in the cycle performance of the battery.

[0046] Furthermore, the thickness of the functional coating in this embodiment is 2-6 μm. For example, the mass ratio of the thiol sodium salt to the binder can be 2 μm, 3 μm, 4 μm, 5 μm, 6 μm, or any value within the range of any two of the above values. If the functional coating is too thin, it cannot play a substantial role, and a small amount of metal ions will diffuse into the negative electrode. If the functional coating is too thick, it will affect the mechanical properties of the battery separator.

[0047] Furthermore, the separator is specifically a porous polymer membrane, which can provide Li + The diaphragm can be freely embedded and removed through the pores, and can be a polypropylene diaphragm (PP) or a polyethylene diaphragm (PE) or a multi-layer composite diaphragm (PP / PE / PP). Since the sodium salt of thiol is weakly acidic, and the polyethylene diaphragm has good chemical stability and can resist acid corrosion, the diaphragm is preferably a polyethylene diaphragm.

[0048] The present invention provides a method for preparing a battery separator using the above separator, comprising the following steps:

[0049] S1. Weigh the sodium thiol salt, the binder and the solvent according to a preset mass ratio, and then disperse the sodium thiol salt, the binder and the solvent at a high speed, and mix them evenly to obtain a functional slurry. Specifically, the solvent is water.

[0050] S2, preparing a diaphragm, and coating the functional slurry on at least one side of the diaphragm;

[0051] S3, baking and drying the diaphragm coated with the functional slurry to form a functional coating on at least one side surface of the diaphragm to obtain the above-mentioned diaphragm.

[0052] It should be noted that the battery separator prepared by the above preparation method has enhanced oxidation resistance on the surface of the battery separator due to the presence of mercapto groups, effectively inhibits the yellowing of the battery separator, improves the ionic conductivity of the battery separator, and ensures the service life and safety of the battery.

[0053] In addition, the thiol sodium salt in the functional coating can also complex the positive electrode metal ions to prevent the positive electrode metal ions from entering the negative electrode area, causing the negative electrode to produce SEI film thickening and lithium ion accumulation problems, resulting in an increase in the internal resistance of the battery and lithium precipitation problems, thereby causing the battery's electrical performance to decline.

[0054] At the same time, due to the hydrophilicity of thiol sodium salts, the wettability of the electrolyte is effectively improved. In addition, the sodium ions contained in thiol sodium salts can reduce the sodium loss in the first cycle of charge and discharge, and improve the first cycle coulomb efficiency.

[0055] Optionally, in step S1, the mass ratio of the thiol sodium salt, the binder and the solvent is 40 to 60:5 to 20:20 to 40. Exemplarily, the mass ratio of the thiol sodium salt, the binder and the solvent can be 40:5:20, 40:10:30, 40:15:30, 40:20:40, 50:5:20, 50:10:20, 50:15:30, 50:20:40, 60:5:40, 60:10:30, 60:15:30, 60:20:20 or any value within the range of any two of the above values. Adding a solvent to the functional slurry can make the slurry evenly dispersed, so that it is convenient to form a uniformly distributed functional coating on the diaphragm in the later stage.

[0056] Furthermore, step S2 specifically includes:

[0057] Prepare the diaphragm and coat the functional slurry on the surface of the diaphragm facing the positive electrode of the battery. It complexes the metal ions and prevents the metal ions from entering the negative electrode. When the positive electrode is delithiated, O will escape from the lattice in the form of free radicals, which is extremely oxidizing. It is necessary to prevent the diaphragm from oxidation.

[0058] Furthermore, in step S2, there are various coating methods for the functional slurry, including roller coating, spray gun spraying, thermal spraying technology, electrodeposition coating, etc. Preferably, roller coating and spray gun spraying have simple processes, easy control of parameters, low labor costs, and are conducive to mass production, and the coating thickness is uniform and the utilization rate is high.

[0059] Furthermore, in step S3, the baking and drying temperature of the binder is generally 80-120°C, and the baking and drying time is generally 3-8 hours. The specific baking and drying temperature and baking and drying time need to be determined according to the coating thickness, the type and amount of the binder. Too long baking and drying time and too high baking and drying temperature may cause the binder to be over-dried, affecting its molding effect; while too short baking and drying time and too low baking and drying temperature may not completely remove the moisture in the material.

[0060] The preferred baking and drying temperature is 90-100°C and the baking and drying time is 4-6 hours, ensuring that the moisture is completely removed while effectively forming.

[0061] See also Figure 1 The present invention provides a battery, comprising the above-mentioned electrode assembly.

[0062] Preferably, the above-mentioned battery is a ternary lithium battery.

[0063] Furthermore, the battery in this embodiment also includes an electrolyte, the electrolyte includes a solvent and a solute, the solute is generally lithium hexafluorophosphate, and the solvent includes at least one of ethylene carbonate (EC), diethyl carbonate (DEC), dimethyl carbonate (DMC), ethyl methyl carbonate (EMC), and vinylene carbonate (VC). For example, it can be EC+EMC+DEC+VC, EC+DMC+EMC+VC, EC+EMC+DEC, EC+DMC+EMC. Such solvents can form a stable negative electrode SEI film at the negative electrode, form a strongly protective interface, resist the influence of metal ions and oxygen on the negative electrode, increase the reaction time of thiol sodium salts, and thus cooperate with thiol sodium salts to improve the electrical performance of the battery.

[0064] Preferably, the solvent in the electrolyte includes VC. A certain amount of VC can promote the solvation rate of sodium ions in the thiol sodium salt and the diffusion of sodium ions, thereby improving the coulombic efficiency.

[0065] The above is a detailed description of a battery separator, a method for preparing the battery separator, and a specific structure and specific steps of the battery in the present invention. The preparation method of the battery separator will be further described below with multiple embodiments and comparative examples.

[0066] See also Figure 1 The present invention provides an electrical device, comprising the above-mentioned battery.

[0067] The technical solution of the present invention is further described in detail below in conjunction with several preferred embodiments and drawings. This embodiment is implemented on the premise of the technical solution of the invention, and a detailed implementation method and specific operation process are given, but the protection scope of the present invention is not limited to the following embodiments.

[0068] Unless otherwise specified, the experimental materials used in the following examples can be purchased from conventional biochemical reagent companies.

[0069] Embodiment 1

[0070] A method for preparing a battery separator comprises the following steps:

[0071] S1: Sodium dimercaptopropane sulfonate, polyvinylidene fluoride and water are weighed in a mass ratio of 40:20:40, dispersed at high speed, and mixed evenly to obtain a functional slurry;

[0072] S2: The functional slurry is evenly coated on the surface of the 12 μm thick PE separator facing the positive electrode of the battery, and the coating thickness of the functional slurry is 6 μm;

[0073] S3. The coated PE separator is vacuum-baked and dried at 100° C. for 6 hours to obtain a battery separator.

[0074] Embodiment 2

[0075] A method for preparing a battery separator comprises the following steps:

[0076] S1: Sodium dithiosuccinate, polyvinylidene fluoride and water are weighed in a mass ratio of 60:20:20, dispersed at high speed, and mixed evenly to obtain a functional slurry;

[0077] S2: The functional slurry is evenly coated on the surface of the 12 μm thick PE separator facing the positive electrode of the battery, and the coating thickness of the functional slurry is 2 μm;

[0078] S3. The coated PE separator is vacuum-baked and dried at 100° C. for 4 hours to obtain a battery separator.

[0079] Embodiment 3

[0080] A method for preparing a battery separator comprises the following steps:

[0081] S1: Sodium dimercaptopropane sulfonate, polyvinylidene fluoride and water are weighed in a mass ratio of 50:15:35, dispersed at high speed, and mixed evenly to obtain a functional slurry;

[0082] S2: The functional slurry is evenly coated on the surface of the 12 μm thick PE separator facing the positive electrode of the battery, and the coating thickness of the functional slurry is 4 μm;

[0083] S3. The coated PE separator is vacuum-baked and dried at 100° C. for 4 hours to obtain a battery separator.

[0084] Embodiment 4

[0085] A method for preparing a battery separator comprises the following steps:

[0086] S1: Sodium dimercaptopropane sulfonate, polyvinylidene fluoride and water are weighed in a mass ratio of 50:15:35, dispersed at high speed, and mixed evenly to obtain a functional slurry;

[0087] S2: The functional slurry is evenly coated on the surface of the 12 μm thick PE separator facing the positive electrode of the battery, and the coating thickness of the functional slurry is 2 μm;

[0088] S3. The coated PE separator is vacuum-baked and dried at 100° C. for 4 hours to obtain a battery separator.

[0089] Embodiment 5

[0090] A method for preparing a battery separator comprises the following steps:

[0091] S1: Sodium dimercaptopropane sulfonate, polyvinylidene fluoride and water are weighed in a mass ratio of 50:15:35, dispersed at high speed, and mixed evenly to obtain a functional slurry;

[0092] S2: The functional slurry is evenly coated on the surface of the 12 μm thick PE separator facing the positive electrode of the battery, and the coating thickness of the functional slurry is 6 μm;

[0093] S3. The coated PE separator is vacuum dried at 100° C. for 4 h to obtain a battery separator.

[0094] Embodiment 6

[0095] A method for preparing a battery separator comprises the following steps:

[0096] S1: Sodium 3-mercapto-1-propanesulfonate, polyvinylidene fluoride and water are weighed in a mass ratio of 50:15:35, dispersed at high speed, and mixed evenly to obtain a functional slurry;

[0097] S2: The functional slurry is evenly coated on the surface of the 12 μm thick PE separator facing the positive electrode of the battery, and the coating thickness of the functional slurry is 4 μm;

[0098] S3. The coated PE separator is vacuum-baked and dried at 100° C. for 4 hours to obtain a battery separator.

[0099] Embodiment 7

[0100] A method for preparing a battery separator comprises the following steps:

[0101] S1: Weigh 5-mercapto-1,2,3-triazole monosodium, polyvinylidene fluoride and water in a mass ratio of 50:15:35, disperse at high speed, and mix well to obtain a functional slurry;

[0102] S2: The functional slurry is evenly coated on the surface of the 12 μm thick PE separator facing the positive electrode of the battery, and the coating thickness of the functional slurry is 4 μm;

[0103] S3. The coated PE separator is vacuum-baked and dried at 100° C. for 4 hours to obtain a battery separator.

[0104] Embodiment 8

[0105] A method for preparing a battery separator comprises the following steps:

[0106] S1: Weigh 5-mercapto-1,2,3-triazole monosodium, polyvinylidene fluoride and water in a mass ratio of 50:15:35, disperse at high speed, and mix well to obtain a functional slurry;

[0107] S2: The functional slurry is evenly coated on the surface of the 12 μm thick PE separator facing the positive electrode of the battery, and the coating thickness of the functional slurry is 4 μm;

[0108] S3. The coated PE separator is vacuum-baked and dried at 80° C. for 4 h to obtain a battery separator.

[0109] Embodiment 9

[0110] A method for preparing a battery separator comprises the following steps:

[0111] S1: Weigh 5-mercapto-1,2,3-triazole monosodium, polyvinylidene fluoride and water in a mass ratio of 50:15:35, disperse at high speed, and mix well to obtain a functional slurry;

[0112] S2: The functional slurry is evenly coated on the surface of the 12 μm thick PE separator facing the positive electrode of the battery, and the coating thickness of the functional slurry is 4 μm;

[0113] S3. The coated PE separator is vacuum-baked and dried at 120° C. for 4 h to obtain a battery separator.

[0114] Embodiment 10

[0115] A method for preparing a battery separator comprises the following steps:

[0116] S1: Sodium dimercaptopropane sulfonate, polyvinylidene fluoride and water are weighed in a mass ratio of 50:15:35, dispersed at high speed, and mixed evenly to obtain a functional slurry;

[0117] S2: The functional slurry is evenly coated on the surface of the 12 μm thick PP separator facing the positive electrode of the battery, and the coating thickness of the functional slurry is 4 μm;

[0118] S3. The coated PP separator was vacuum-baked and dried at 100° C. for 4 h to obtain a battery separator.

[0119] Embodiment 11

[0120] A method for preparing a battery separator comprises the following steps:

[0121] S1: Sodium dimercaptopropane sulfonate, polyvinylidene fluoride and water are weighed in a mass ratio of 30:20:50, dispersed at high speed, and mixed evenly to obtain a functional slurry;

[0122] S2: The functional slurry is evenly coated on the surface of the 12 μm thick PP separator facing the positive electrode of the battery, and the coating thickness of the functional slurry is 4 μm;

[0123] S3. The coated PP separator was vacuum-baked and dried at 100° C. for 4 h to obtain a battery separator.

[0124] Embodiment 12

[0125] A method for preparing a battery separator comprises the following steps:

[0126] S1: Sodium dimercaptopropane sulfonate, polyvinylidene fluoride and water are weighed in a mass ratio of 65:25:10, dispersed at high speed, and mixed evenly to obtain a functional slurry;

[0127] S2: The functional slurry is evenly coated on the surface of the 12 μm thick PP separator facing the positive electrode of the battery, and the coating thickness of the functional slurry is 4 μm;

[0128] S3. The coated PP separator was vacuum-baked and dried at 100° C. for 4 h to obtain a battery separator.

[0129] Embodiment 13

[0130] A method for preparing a battery separator comprises the following steps:

[0131] S1: Sodium dimercaptopropane sulfonate, polyvinylidene fluoride and water are weighed in a mass ratio of 40:20:40, dispersed at high speed, and mixed evenly to obtain a functional slurry;

[0132] S2: The functional slurry is evenly coated on a 12 μm thick PE diaphragm. Functional coatings and 3 are provided on both sides of the diaphragm 1. The thickness A of the functional coating near the cathode side is 4 μm, and the thickness B of the functional coating 3 near the anode side is 3 μm.

[0133] S3. The coated PE separator is vacuum-baked and dried at 100° C. for 6 hours to obtain a battery separator.

[0134] Embodiment 14

[0135] A method for preparing a battery separator comprises the following steps:

[0136] S1: Sodium dimercaptopropane sulfonate, polyvinylidene fluoride and water are weighed in a mass ratio of 40:20:40, dispersed at high speed, and mixed evenly to obtain a functional slurry;

[0137] S2: The functional slurry is evenly coated on a 12 μm thick PE diaphragm. The functional coating is provided on both sides of the diaphragm 1. The coating thickness gradually increases from 2 μm to 6 μm as the tension of the pole piece decreases.

[0138] S3. The coated PE separator is vacuum-baked and dried at 100° C. for 6 hours to obtain a battery separator.

[0139] Comparative Example 1:

[0140] The invention provides a PE battery separator with a thickness of 12 μm in the prior art.

[0141] Comparative Example 2:

[0142] A method for preparing a battery separator comprises the following steps:

[0143] S1: Sodium dimercaptopropane sulfonate, polyvinylidene fluoride and water are weighed in a mass ratio of 50:15:35, dispersed at high speed, and mixed evenly to obtain a functional slurry;

[0144] S2: The functional slurry is evenly coated on the surface of the 12 μm thick PE separator facing the positive electrode of the battery, and the coating thickness of the functional slurry is 8 μm;

[0145] S3. The coated PE separator is vacuum-baked and dried at 100° C. for 6 hours to obtain a battery separator.

[0146] Comparative Example 3:

[0147] A method for preparing a battery separator comprises the following steps:

[0148] S1: Sodium dimercaptopropane sulfonate, polyvinylidene fluoride and water are weighed in a mass ratio of 50:15:35, dispersed at high speed, and mixed evenly to obtain a functional slurry;

[0149] S2: The functional slurry is evenly coated on the surface of the 12 μm thick PE separator facing the positive electrode of the battery, and the coating thickness of the functional slurry is 1 μm;

[0150] S3. The coated PE separator is vacuum dried at 100° C. for 6 h to obtain a battery separator.

[0151] Test Case

[0152] 1. Preparation of batteries

[0153] Negative electrode sheet: 95.5 wt.% graphite, 2 wt.% styrene-butadiene rubber latex (SBR), 1.5 wt.% sodium carboxymethyl cellulose (CMC), and 1 wt.% conductive carbon black (SP) were dispersed in water, then coated on 8 μm copper foil and dried to make the negative electrode.

[0154] Positive electrode sheet: 96 wt.% Li(NiCoMn)O2 positive electrode material, 1 wt.% conductive carbon black (SP), 1 wt.% carbon nanotubes (CNT), and 2 wt.% polyvinylidene fluoride (PVDF) were dispersed and dissolved in N-methylpyrrolidone, then coated on 12um aluminum foil and dried to make the positive electrode.

[0155] Battery preparation: The positive electrode sheet, battery separator and negative electrode sheet are wound to obtain a battery cell; the battery cell is installed in an aluminum shell and injected with electrolyte to seal it to obtain a square aluminum shell sodium ion battery.

[0156] Electrolyte: 93.5 wt.% lithium hexafluorophosphate (1 mol / L), 1.5 wt.% EC (ethylene carbonate), 1.5 wt.% EMC (ethyl methyl carbonate), 1.5 wt.% DEC (diethyl carbonate), and 2 wt.% VC (vinylene carbonate) were fully mixed to obtain the electrolyte of the battery.

[0157] 2. Test methods

[0158] 1C / 1C cycle life test: The sodium ion aluminum shell batteries prepared in the above embodiments and comparative examples were taken respectively, and the capacity was divided under the test conditions of 0.1C rate, charge cut-off voltage 4.35V, and discharge cut-off voltage 2.8V at 25°C, and then a 1C / 1C cycle test was carried out at 25°C (charge cut-off voltage 4.35V, discharge cut-off voltage 2.8V).

[0159] The battery was disassembled after 1000 cycles of 1C / 1C to obtain the separator, negative electrode sheet and lithium deposition in the corners after 1000 cycles. The negative electrode sheet was photographed with a scanning electron microscope to measure the average SEI film thickness. For specific results, please refer to Table 1.

[0160] Table 1: Yellowing of the diaphragm after 1000 cycles, first cycle discharge capacity, first cycle coulomb efficiency and 1C / 1C cycle life

[0161]

[0162] The yellowing phenomenon corresponds to the antioxidant effect of the thiol sodium salt of the functional coating, the first-cycle discharge specific capacity and coulomb efficiency correspond to the sodium supplementation effect of the thiol sodium salt of the functional coating, and the cycle life corresponds to the wettability of the electrolyte. As can be seen from Table 1 above, the antioxidant properties, first-cycle coulomb efficiency, and cycle life of the battery separators prepared by the battery separator preparation methods of Examples 1-13 of the present invention are significantly higher than those of the existing battery separators in Comparative Example 1, while the SEI film thickness is significantly lower than that of the existing battery separators in Comparative Example 1. In Comparative Examples 2 and 3, the thickness of the functional coating is 1 μm and 8 μm, respectively, and the coating thickness is not within the range of the functional coating thickness defined by the present invention. Therefore, many properties of the battery separators of Comparative Examples 2 and 3 are slightly lower than those of the battery separator in Example 3. In addition, it can be seen from Examples 10-12 that after using PP material as the separator, the separator exhibits a slight yellowing phenomenon. Therefore, in this embodiment, PE material is preferably used to make the separator.

[0163] The above is a detailed introduction to an electrode assembly, a battery and an electrical device provided by the present invention. For a person skilled in the art, according to the concept of the embodiments of the present invention, there may be changes in the specific implementation methods and application scopes. In summary, the content of this specification should not be understood as a limitation on the present invention.

Claims

1. A battery, characterized in that: The invention comprises an electrode assembly and an electrolyte, wherein the electrolyte comprises vinylene carbonate; The electrode assembly comprises a positive electrode sheet, a negative electrode sheet and a separator between the positive electrode sheet and the negative electrode sheet, the positive electrode sheet comprises positive electrode metal ions and oxygen elements, and a functional coating is arranged on the separator, wherein the functional coating comprises a thiol sodium salt and a binder; The functional coating is provided on one surface of the diaphragm facing the positive electrode sheet and on one surface of the diaphragm facing the negative electrode sheet; the thickness of the functional coating on the one surface of the diaphragm facing the positive electrode sheet is A, and the thickness of the functional coating on the one surface of the diaphragm facing the negative electrode sheet is B, wherein: 6μm≥A>B≥2μm.

2. The battery according to claim 1, characterized in that The positive electrode sheet, the negative electrode sheet and the separator are wound to form the electrode assembly, and the electrode assembly has a straight portion and a bent portion, and both the bent portion and the straight portion are provided with the functional coating; the thickness of the functional coating at the bent portion is C, and the thickness of the functional coating at the straight portion is D, wherein 6μm≥C>D≥2μm.

3. The battery according to claim 2, characterized in that In the bent portion, the thickness of the functional coating on the surface of the side of the diaphragm facing the positive electrode sheet is E, and the thickness of the functional coating on the surface of the side of the diaphragm facing the negative electrode sheet is F. In the straight portion, the thickness of the functional coating on the surface of the side of the diaphragm facing the positive electrode sheet is G, and the thickness of the functional coating on the surface of the side of the diaphragm facing the negative electrode sheet is H, wherein 6μm≥E>F>G>H≥2μm.

4. The battery according to any one of claims 1 to 3, characterized in that: The thiol sodium salts include sodium dimercaptopropanesulfonate, sodium dimercaptosuccinate, sodium dimercaptosuccinate, monosodium 5-mercapto-1,2,3-triazole, sodium 3-mercapto-1-propanesulfonate, sodium thioglycolate, monosodium 2-mercaptoethanol, monosodium 2,4,6-trimercapto-1,3,5-s-triazine, sodium mercaptobenzothiazole, disodium 1-sulfonic acid methyl-5-mercaptotetrazole, disodium 5-mercapto-1-sulfonic acid methyl tetrazole, disodium 2,5-dimercaptothiadiazole, sodium 1-2-hydroxyethyl-5-mercapto-1H-tetrazole, sodium 3-mercapto-1-propanesulfonate, sodium 2-thiopyridine nitrogen oxide, tetrasodium 1,2,4,5-tetramercaptobenzene, sodium 1-methyl-5-mercaptotetrazole, trisodium mercapto-s-triazine; and / or, The binder includes one or more of polytetrafluoroethylene, polyvinylidene fluoride, styrene-butadiene rubber, sodium carboxymethyl cellulose, polyacrylate, and polyacrylic acid; and / or, In the functional coating, the mass ratio of the mercapto sodium salt to the binder is 40-60:5-20.

5. An electrical device, characterized in that: Comprising the battery according to any one of claims 1 to 4.

Citation Information

Patent Citations

  • Battery separators comprising chemical additives and / or other components

    CN107431167A

  • Anti-aging type PE color master batch preparation method

    CN107841027A

  • Sodium supplementing composition and sodium ion battery

    CN115117558A